What is the answer to 3x+2-x=11x-9
2 answers:
3x+2−x=11x−9
Step 1: Simplify both sides of the equation.
3x+2−x=11x−93x+2+−x=11x+−9(3x+−)(2)=11x−9
(Combine Like Terms)
2x+2=11x−92x+2=11x−9
Step 2: Subtract 11x from both sides.
2x+2−11x=11x−9−11x−9x+2=−9
Step 3: Subtract 2 from both sides.
−9x+2−2=−9−2−9x=−11
Step 4: Divide both sides by -9.
−9x−9=−11−9x=119
ANSWER: 11/9
Hope it helps
1.22222222 (1.2 repeated)
You might be interested in
Check the picture below
notice, the length cannot be a negative value.. so is not -17
10 times 12 is 120 times 24 equals 2,880 sq2
Answer:
C
Step-by-step explanation:
#1 answer is D and #2 answer is D also